Contemporary Magnetic Removable Partial Denture Utilizing a Novel Ultra-Thin Magnetic Attachment System - Adityakrisna Yoshi Putra Wigianto; Yuichi Ishida; Kohei Kamoi; Takaharu Goto; Kazumitsu Sekine; Megumi Watanabe; Tetsuo Ichikawa (Dentistry Journal)
Background/Objectives: Recently, a novel magnetic attachment system was introduced to improve performance. Using the same technology, a new ultra-thin magnetic attachment (UTMA) was possible to produce. This study aimed to evaluate the feasibility of a magnet-retained telescopic partial denture (MTPD) utilizing the new UTMA. Methods: This in vitro study was performed using a titanium master model representing prepared lower first-premolar and second-molar abutment teeth. The inner crowns (ICs) (h: 4 mm, 4° taper) and four-unit MTPDs were fabricated via computer-aided design/computer-aided manufacturing (CAD/CAM) using zirconia. A Ø4 mm UTMA system (magnet assembly and keeper thickness: 0.6 mm and 0.4 mm, respectively) was cemented into the MTPD and the ICs using dual-cure resin cement. A load of 100 N was applied along with 10,000 insertion–removal cycles. The MTPD retentive force was measured before and after every set of 1000 cycles. Stability tests and surface morphology evaluations were conducted before and after cycling. A paired t-test (α = 0.05) was used to observe statistical differences. Results: The average retentive force of the MTPD was 6.86 ± 0.63 N and did not change significantly (p > 0.05) following the load cycles (6.66 ± 0.79 N). The MTPD demonstrated adequate stability under the occlusal load. Minimal deformations were observed on the magnet assemblies, keepers, ICs, and MTPD surfaces after the load tests. Conclusions: Considering the limitations of this study, an MTPD utilizing novel UTMAs fabricated through a digital workflow demonstrated adequate retentive force, stability, and durability for clinical use.